Appraisal on the Factors Affecting Declining Standard of Primary Education Among the Communities of Adamawa State, Nigeria - Jada, Hamidu Mohammed; Giginyu, Ali Abdu; Mutah, Muhammad Ali (Profesi Pendidikan Dasar, 2023)
The study assesses the Factors Affecting Declining Standard of Primary Education among the Community of Adamawa State, Nigeria. Education plays an important role in the development of a nation, thus, a nation cannot do without quality education. Primary education is the core of development and progress especially in modern societies. However, the quality of education that helps in ensuring the realization of the aspirations parents hold for their children has fallen below expectation. Therefore, the research investigated the major factors that contributed to the standard of primary education in Adamawa state, Nigeria; this study used Simple Random Sampling in order to ensure that the larger population is well represented. The study involved 1,966 primary schools of Adamawa state and a total of 335 respondents which comprised of 143 school-heads and 192 teachers. Data analysis was conducted using a descriptive analysis technique from the comparison of average questionnaire results based on the variables tested. In general the study indicated that there is positive relationship between school personnel and community in Adamawa state, Nigeria with 3.85 mean score. Finally, the study suggested some of the ways of improving the quality and standard of primary education in Adamawa state, Nigeria.